Non-invasive monitoring of in vitro gastric milk protein digestion kinetics by 1H NMR magnetization transfer. (30th July 2022) - Mayar, Morwarid; Miltenburg, Julie L.; Hettinga, Kasper; Smeets, Paul A.M.; van Duynhoven, John P.M.; Terenzi, Camilla
Highlights: The amount of semi-solid protein detected by NMR magnetization transfer decreases during protein digestion. NMR magnetization transfer can be used to study the breakdown of the milk protein coagulum. Heat-treatment of skim milk results in slower breakdown of the protein coagulum. Magnetization transfer is promising for studying in vivo protein digestion. Abstract: Processing of milk involves heating, which can modify the structure and digestibility of its proteins. In vitro models are useful for studying protein digestion. However, validating these models with in vivo data is challenging. Here, we non-invasively monitor in vitro gastric milk protein digestion by protein-water chemical exchange detected by 1 H nuclear magnetic resonance (NMR) magnetization transfer (MT). We obtained either a fitted composite exchange rate ( CER ) with a relative standard error of ≤10% or the MT ratio ( MTR ) of the intensity without or with an off-resonance saturation pulse, from just a single spectral acquisition. Both CER and MTR, affected by the variation in the amount of semi-solid protons, decreased during in vitro gastric digestion in agreement with standard protein content analyses. The decrease was slower in heated milk, indicating slower breakdown of the coagulum. Our results open the way to future quantification of protein digestion in vivo by MRI.